(untitled) (REMUNOM, 2025)
This article analyzes employers’ legal liability for their employees’ conduct on social media, considering the impacts that personal statements can have on the company’s institutional image. The research adopts a deductive method, based on a literature review, document analysis, and case law, to understand the boundaries between employees’ freedom of expression and the duties of loyalty and good faith that govern the employment relationship. The article discusses employers’ civil liability in light of the Civil Code, the Consolidation of Labor Laws, and the Federal Constitution, assessing the extent to which employers can be held liable for conduct committed outside the workplace. The study seeks to contribute to the legal definition of these situations and the development of preventive strategies that balance employees’ fundamental rights with the protection of corporate trust.